'Heavier the interval than the consummation': bronchial disease in Seán Ó Ríordáin's diaries. Issue 1 (3rd September 2013) - Breathnach, Ciara
Abstract: Narratives of the experience of pulmonary tuberculosis (TB) are relatively rare in the Irish context. A scourge of the early twentieth century, TB was as much a social as a physically debilitating disease that rendered sufferers silent about their experience. Thus, the personal diaries and letters of Irish poet, Seán Ó Ríordáin, (1916–1977) are rare. This article presents translations of his personal papers in a historico-medical context to chronicle Ó Ríordáin's experience of a life marred by respiratory disease. Familiar to generations of schoolchildren are his imaginative poems, whose lively metre punctuated the Irish language curriculum from primary through to secondary schooling; for most they leave an indelible mark. Such buoyant poems however belie the reality of his existence, lived in the shadow of chronic illness, and punctuated with despair over his condition and anxiety about the periods of extended sick leave his illness necessitated. Although despair dominated his diaries and he routinely begged God, Mary, the Saints and the devil for death, they were also the locus where his creativity developed. In his diaries, caricatures of friends and sketches of everyday things nestle among the first lines of some of his most influential poems and quotes from distinguished philosophers and writers. Evocative and tragic, his diaries offer a unique prism to the experience of respiratory disease in Ireland.